Osteopontin is a Prognostic Factor in Patients with Advanced Gastric Cancer - Yazici, Ozan; Dogan, Mutlu; Ozal, Guze; Aktas, Sedef H.; Demirkazik, Ahmet; Utkan, Gungor; Senler, Filiz Cay; Icli, Fikri; Akbulut, Hakan (Combinatorial Chemistry & High Throughput Screening, 2021)
Objective: Osteopontin (OPN), a phosphorylated sialoprotein, has been shown to overexpress in a variety of cancers and to contribute tumor progression and metastasis by increasing cell migration and adhesion. In the current study, we aimed to investigate the prognostic and predictive role of OPN in patients with advanced gastric cancer. Methods: A total of 42 consecutive chemonaive patients with advanced gastric cancer and 29 healthy controls were included. The patients were treated with a modified DCF regimen. The blood samples were obtained before each chemotherapy cycle from the patients and once from the healthy controls. The plasma OPN is measured by ELISA. Results: The overall response and disease stabilization rates were 25% and 72%, respectively. The median serum OPN level of the patient group was significantly higher compared to healthy controls (176.9 ng/ml (range: 41.5 -521.4) vs 64.3 ng/ml (range 42.1-105.3 ng/ml), p<0.0001). The median overall survival time was 7.0 ± 1.1 (95% CI: 4.9–9.2) months and 1-year overall survival rate was 20.8%. The patients who responded to mDCF had lower plasma OPN levels than the non-responding ones (110.7±29.3 ng/mL, 211.9±24.4 ng/mL respectively, p=0.002). The performance status and the plasma OPN levels were found to be significant factors for overall survival in the multivariate analysis (p=0.004 and 0.016, respectively). Conclusion: The serum OPN seems to be a novel significant prognostic and predictive factor in patients with advanced gastric cancer who were treated with DCF regimen.
Keywords: Osteopontin